2011
DOI: 10.5194/acp-11-11103-2011
|View full text |Cite
|
Sign up to set email alerts
|

Observations of nonmethane organic compounds during ARCTAS − Part 1: Biomass burning emissions and plume enhancements

Abstract: Abstract. Mixing ratios of a large number of nonmethane organic compounds (NMOCs) were observed by the Trace Organic Gas Analyzer (TOGA) on board the NASA DC-8 as part of the Arctic Research of the Composition of the Troposphere from Aircraft and Satellites (ARCTAS) field campaign. Many of these NMOCs were observed concurrently by one or both of two other NMOC measurement techniques on board the DC-8: proton-transfer-reaction mass spectrometry (PTR-MS) and whole air canister sampling (WAS). A comparison of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
100
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(112 citation statements)
references
References 78 publications
10
100
2
Order By: Relevance
“…These ratios were determined for fires with different plume ages and various fuel types. Post-emission chemistry is expected to affect enhancement ratios, and Hornbrook et al (2011). previous work has observed an increase in glycolaldehyde relative to CO with plume age (Akagi et al, 2012). The ARCTAS-CARB observations are consistent with the previously reported observations of glycolaldehyde in biomassburning plumes.…”
Section: Arctas-carb 2008supporting
confidence: 82%
See 1 more Smart Citation
“…These ratios were determined for fires with different plume ages and various fuel types. Post-emission chemistry is expected to affect enhancement ratios, and Hornbrook et al (2011). previous work has observed an increase in glycolaldehyde relative to CO with plume age (Akagi et al, 2012). The ARCTAS-CARB observations are consistent with the previously reported observations of glycolaldehyde in biomassburning plumes.…”
Section: Arctas-carb 2008supporting
confidence: 82%
“…A list of biomass- burning plumes encountered by the DC-8 during the ARC-TAS campaign can be found in Hornbrook et al (2011). Possible biomass-burning plumes are identified by time periods of elevated biomass-burning tracer mixing ratios.…”
Section: Arctas-carb 2008mentioning
confidence: 99%
“…These lifetimes are also short enough so that BB emissions are a substantial increase over the ambient concentrations. For these reasons all three species are widely used tracers for BB Hornbrook et al, 2011;Vay et al, 2011).…”
Section: Analysis Methodologymentioning
confidence: 99%
“…Maximum concentrations of these biomass burning tracers as well as plume altitudes are listed in Table 1. Plume identification and back trajectory analysis performed by Hornbrook et al (2011) indicated the 17 April plume examined here was a ∼ 6 day old Siberian forest fire plume. In contrast, measurements during the 29 June case were made directly above an active fire in Saskatchewan, a plume less than 3 h old (Hornbrook et al, 2011).…”
Section: Case Studiesmentioning
confidence: 99%
“…Plume identification and back trajectory analysis performed by Hornbrook et al (2011) indicated the 17 April plume examined here was a ∼ 6 day old Siberian forest fire plume. In contrast, measurements during the 29 June case were made directly above an active fire in Saskatchewan, a plume less than 3 h old (Hornbrook et al, 2011). It is important to note that the 17 April plume was intersected at the top of the spiral profile and it is unclear whether the entire plume was sampled.…”
Section: Case Studiesmentioning
confidence: 99%